Вероятностно-статистическая оценка показателей надежности долот ИСМ - Эфендиев, Г.М.; Аббасов, А.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The lecture is dedicated to probability-statistical analysis for life of “ISM” bits. Based on study of no-failure operation distribution law studies showed that in considered case it’s obey normal low. Going from this, it was proposed to use alternative method of calculating life of bit, used in different applications.